ANALISIS MORFOMETRI DAN BIOLOGI REPRODUKSI ANAPHALIS JAVANICA DAN A.LONGIFOLIA (ASTERACEAE) DI SUMATERA BARAT - Ahmad Taufiq; Syamsuardi Syamsuardi; Ardinis Arbain; Tesri Maideliza; Mansyurdin Mansyurdin (Floribunda, 2013)
Anaphalis javanica and A. longifolia, were collected during the expeditionto Mt. Merapi, Singgalang, Tandikat, and Talang (West Sumatra). Beside two of these species, several individuals of Anaphalis that differs in several characters from the two others species were also found. Based on it, morphometric study and biology reproduction analysis were carried out to clarify their taxonomic classification. Fifty three individuals of Anaphalis were collected and twenty four characters had been observed and measured to define species and morphology variation. Data analysis revealed that the alien species were defined as a natural hybrid of A. javanica and A. longifolia. There was no significant difference that number and morphology of pollens among populations as well as those two species studied. Based on the P/O ratio analysis indicated that breeding system of A. javanica and A. longifolia were facultative xenogamy. The same ornamentation (echinate) in both of two species suggested that the natural hybridization between two species was possible.